Reproductive outcome after surgical sperm retrieval and intracytoplasmic sperm injection in couples with male factor sub fertility: a 10-year retrospective observational study - Sebastian, Nikhil; Suraj, Jayalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: To evaluate surgical sperm retrieval (SSR) rate in men with obstructive azoospermia (OA) and non-obstructive azoospermia (NOA) and to compare clinical pregnancy rate (CPR) following ICSI. It was a retrospective observational study done at Dream Flower IVF Centre, Kasaragod, Kerala, India. Methods: The 124 azoospermic men who underwent SSR along with intra cytoplasmic sperm injection (ICSI) between June 2013 to May 2024 were included in the study. OA and NOA were classified depending on the history, physical examination, ultrasonography and laboratory findings. Analysis of data on SSR rate and reproductive outcome following ICSI was done. Results: A total of 124 male patients presented with azoospermia of which 52 patients (41.93%) had OA while 72 patients (58.06%) had NOA. The SSR rate was significantly higher in OA (100%) when compared to NOA (48.6%; p<0.05). The follicle stimulating hormone (FSH) level was significantly lower in participants with OA (5.2±2.0) when compare to NOA (25.1±15.2; p<0.05). ICSI using surgically retrieved spermatozoa was done in 90 couples. We failed to retrieve sperms in 34 (28.41%) patients, of which 27 couples opted for donor sperm (DS) for ICSI. The CPR was 55.8% and 39.5% in OA and NOA respectively. No significant difference in CPR (p=0.286), miscarriage rate (p=0.056) or live birth rate (p=0.904) were observed among the three groups. Conclusions: Azoospermic men can be counselled about the probability of successful sperm retrieval as well as their likelihood to father their biological child following ICSI without the need of donor spermatozoa.